Erratum: Characterization of Mechanically Matched Hydrogel Coatings to Improve the Biocompatibility of Neural Implants. Issue 1 (December 2017) - Spencer, Kevin; Sy, Jay; Ramadi, Khalil; Graybiel, Ann; Langer, Robert; Cima, Michael
A correction to this article has been published and is linked from the HTML version of this paper. The error has not been fixed in the paper.